Regulasi Mandiri Transportasi Online Dalam Pembayaran Pesanan Makanan Atas Konsumen Yang Ingkar Janji - Erwin Asmadi (Universitas Muhammadiyah Sumatera Utara, 2019)
The implementation of consumer protection is so detailed that it is regulated through the Consumer Protection Act. But the loss of the online transportation application service providers is less in the spotlight, let alone driver losses as parties affiliated with the service application. This paper presents the disadvantages experienced by drivers and how online service application service companies are able to solve these problems. Especially controlling the implementation of online transportation applications through self-regulation made by online transportation application provider companies (providers of electronic systems). The regulation is subject to and may not conflict with the laws and regulations in force in Indonesia. In practice, the driver loss is often not questioned, but as long as there is proof of purchase, assistance or replacement is possible to the extent possible by the application service provider.